Some of Extreme Eclipsing Binaries among Hot B Stars - Kvernadze, T.; Chargeishvili, K.; Kvaratskhelia, O.; Kurkhuli, G.; Kozlov, V.; Kapanadze, G.
In this work we used the catalog of spectral and luminosity classes of 6,037 stars in the direction of the Galaxy anticenter and selected a subsample list of 2067 stars covering whole B spectral and luminosity classes including peculiar B stars. We used TESS Quick-Look Pipeline (QLP) light curves for all those stars from the Mikulski Archive for Space Telescopes (MAST) database in FITS format tables and processed all of them using interactive python code. To avoid contamination of variability from neighboring stars we analyzed light curves per pixel for each star and extracted a light curve free of any contamination. For pulsation eclipsing binary stars we estimated frequency spectra using Lomb-Scargle Periodograms and excluded it from a source light curve to get a pure transit signal. We used than Transit Least Squares algorithm to determine the periods and epochs of eclipsing events and built the phase curves. As a result we are presenting 23 new detached eclipsing binary stars, 11 of which have high eccentricity and 12 of them show pulsation signals.
Keywords: Astronomy